2012
DOI: 10.1186/1479-5868-9-125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meal preparation training on body weight, glycemia, and blood pressure: results of a phase 2 trial in type 2 diabetes

Abstract: BackgroundModest reductions in weight and small increases in step- related activity (e.g., walking) can improve glycemic and blood pressure control in type 2 diabetes mellitus (DM2). We examined changes in these parameters following training in time- efficient preparation of balanced, low- energy meals combined with pedometer- based step count monitoring.MethodsSeventy- two adults with DM2 were enrolled in a 24- week program (i.e., 15 three- hour group sessions). They prepared meals under a chef’s supervision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
3
30
0
1
Order By: Relevance
“…The difference of HbA1c in the intervention and the control groups were −0.29% and +0.09%, respectively with a statistically significant difference consistent with a previous study regarding the effect of changes in diet on HbA1c for 3 months which found the difference of HbA1c in the intervention was −0.83% with a statistically significant difference [21]. In other previous studies, meal preparation training also decreased HbA1c (0.3%) after 6 month follow up [22] and lifestyle counseling in the primary care setting also decreased HbA1c [23]. However, the effect of changes in supportive telephone counseling on HbA1c for 18 months did not present a statistically significant difference between the intervention and the control groups [24].…”
Section: Discussionsupporting
confidence: 86%
“…The difference of HbA1c in the intervention and the control groups were −0.29% and +0.09%, respectively with a statistically significant difference consistent with a previous study regarding the effect of changes in diet on HbA1c for 3 months which found the difference of HbA1c in the intervention was −0.83% with a statistically significant difference [21]. In other previous studies, meal preparation training also decreased HbA1c (0.3%) after 6 month follow up [22] and lifestyle counseling in the primary care setting also decreased HbA1c [23]. However, the effect of changes in supportive telephone counseling on HbA1c for 18 months did not present a statistically significant difference between the intervention and the control groups [24].…”
Section: Discussionsupporting
confidence: 86%
“…Elsewhere, a 24-week meal preparation intervention was conducted in T2D patients. The program successfully reduced weight, A1c, and there was a trend toward lower blood pressure but sodium intake was not documented [37]. Our study showed a significant reduction in systolic blood pressure by 4.1 mm Hg and diastolic blood pressure by 1.7 mm Hg.…”
Section: Discussionmentioning
confidence: 68%
“…With respect to item (6), as a starting point for discussion, we described an intervention approach that we have pilot tested in adults with DM2 [16] that included meal preparation training (‘cooking lessons’) combined with nutrition education and pedometer-based self-monitoring. This approach has demonstrated clinically-important improvements in glycemic control (i.e., 0.3% reduction over 6 months in hemoglobin A1C) that correlate with small weight changes.…”
Section: Methodsmentioning
confidence: 99%
“…Time-efficient, balanced meals were prepared in small groups under a chef’s supervision, with concurrent discussion with a dietitian. This was combined with pedometer-based self-monitoring [16]. Of note, neither the moderator nor co-moderator of the focus groups was involved in this latter study.…”
Section: Methodsmentioning
confidence: 99%